2020
DOI: 10.1016/j.ebiom.2020.102992
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial damage and a thin intercellular fibrin network promote haemorrhage in acute promyelocytic leukaemia

Abstract: Background The role of vascular endothelium in acute promyelocytic leukaemia (APL) remains unknown. We aimed to investigate the mechanisms by which APL cells interact with endothelial cells (ECs) and to further explore how the endothelium affects bleeding as well as therapeutic interventions. Method APL cells and an original APL cell line, NB4 cells, were used for experiments. The effects of leukaemic cells on ECs were analyzed in vitro and in vivo. Moreover, the endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Each of the donors signed an informed consent form. APL was diagnosed based on clinical data, morphology, cytochemistry, immunology, cytogenetics and molecular pathology testing, or confirmation of the presence of the t ( 15 , 17 ) (PML-RARα) fusion gene ( 26 ). Table 1 summarizes main clinical characteristics of patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the donors signed an informed consent form. APL was diagnosed based on clinical data, morphology, cytochemistry, immunology, cytogenetics and molecular pathology testing, or confirmation of the presence of the t ( 15 , 17 ) (PML-RARα) fusion gene ( 26 ). Table 1 summarizes main clinical characteristics of patients.…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that pathological neutrophils, APL cells or NB4 cells, cause bleeding by damaging endothelium in APL ( 17 ). However, the role of ETs, a product of neutrophils, in endothelial injury- related hemorrhage is unclear in APL.…”
Section: Introductionmentioning
confidence: 99%
“…The depletion of neutrophils has been shown to reverse experimental thrombosis ( 9 , 10 ). Another study reported that neutrophils produce tissue factor (TF) and contribute to the formation of thrombosis in vivo and in vitro ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we verified that NET deposition is more abundant in cancer tissues of patients with GC, accompanied by significant NET infiltration around miANGPT2cro vessels. Related studies have also confirmed that NETs can damage endothelial cells and recruit platelets to the injured site, leading to the formation of deep venous thrombosis ( 36 , 37 ). This evidence shows that NETs can affect endothelial cells and trigger the onset and development of GC in the TME.…”
Section: Discussionmentioning
confidence: 87%